Signifikansi Pendekatan Fenomenologi terhadap Dinamika Religious Studies: Kajian atas Pemikiran Dauglas Allen - Susanto, Edi (Program Pascasarjana UIN Sunan Ampel Surabaya, 2006)
Researches in religious studiesâas well as Islamic studiesâoften useapproaches that lead to simplistic and reductionist conclusions. This indeed runs counterto the substance of pluralism which is rich in its symbol and intensional representation.This article is an effort to describe the significance of the phenomenological approach tothe study of religion by using the works of Douglas Allen as the main entrance. In doingso, it tries to understand religious data from the epoche, eidetic and verstehen perspectivesin a way that just and balanced conclusion may be reached.